2003
DOI: 10.1086/368130
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Rhesus Monkeys Have Lower Type 2 Cytokine Responses than Adults after Primary Infection withSchistosoma mansoni

Abstract: Adults and children have differences in their susceptibility to schistosomiasis. The relative influences of agedependent innate resistance and acquired immunity in the differences between susceptibility to schistosomiasis are difficult to assess in humans. Therefore, we exposed juvenile and adult female rhesus monkeys to primary infection with Schistosoma mansoni. In contrast to the adult animals, the juvenile rhesus monkeys had low levels of interleukin (IL)-4 and IL-5 production by peripheral blood mononucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Juvenile mice are more susceptible than adult mice to primary N. brasiliensis infection Previous studies in juvenile and adult rhesus monkeys demonstrated an increased susceptibility to primary S. mansoni infection in younger animals (21,22). To explore the immunological basis of this, we initially sought to use murine S. mansoni infections, a widely used animal model of many aspects of human schistosome infection (31).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Juvenile mice are more susceptible than adult mice to primary N. brasiliensis infection Previous studies in juvenile and adult rhesus monkeys demonstrated an increased susceptibility to primary S. mansoni infection in younger animals (21,22). To explore the immunological basis of this, we initially sought to use murine S. mansoni infections, a widely used animal model of many aspects of human schistosome infection (31).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, rhesus monkeys were used to show that juveniles are more susceptible to primary infection with S. mansoni relative to comparably infected adult monkeys, which is associated with a marked defect in the generation of a range of helminth-specific type 2 responses in younger monkeys (21). The defective ability of juvenile animal hosts to initiate such an im- mune response to helminths is not restricted to rhesus monkeys; it is also seen in rats, with a delayed worm expulsion in juvenile rats following primary infection with N. brasiliensis or S. mansoni (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations